Disruption of REC8 in Meiosis I led to watermelon seedless. (October 2022) - Cao, Lihong; Li, Chuang; Li, Hewei; Wang, Zheng; Jiang, Yanxin; Guo, Yalu; Sun, Piaoyun; Chen, Xi; Li, Qingqing; Tian, Haoran; Li, Zheng; Yuan, Li; et al.
Abstract: In triploid watermelon ( Citrullus lanatus ), the homologous chromosomes of germ cells are disorder during meiosis, resulting in the failure of seeds formation and producing seedless fruit. Therefore, mutating the genes specifically functioning in meiosis may be an alternative way to achieve seedless watermelon. REC8, as a key component of the cohesin complex in meiosis, is dramatically essential for sister chromatid cohesion and chromosome segregation. However, the role of REC8 in meiosis has not yet been characterized in watermelon. Here, we identified ClREC8 as a member of RAD21/REC8 family with a high expression in male and female flowers of watermelon. In situ hybridization analysis showed that ClREC8 was highly expressed at the early stage of meiosis during pollen formation. Knocking out ClREC8 in watermelon led to decline of pollen vitality. After pollinating with foreign normal pollen, the ovaries of ClREC8 knockout lines could inflate normally but failed to form seeds. We further compared the meiosis chromosomes of pollen mother cells in different stages between the knockout lines and the corresponding wild type. The results indicated that ClREC8 was required for the monopolar orientation of the sister kinetochores in Meiosis I . Additionally, transcriptome sequencing (RNA-seq) analysis between WT and the knockout lines revealed that the disruption of ClREC8 caused the expression levels of mitosis-related genes and meiosis-related genes to decrease. Our results demonstrated ClREC8 has a specific role in Meiosis I of watermelon germ cells, and loss-of-function of the ClREC8 led to seedless fruit, which may provide an alternative strategy to breed cultivars with seedless watermelon. Highlights: ClREC8 is identified as a member of RAD21/REC8 family. ClREC8 is required for the monopolar orientation of kinetochore in Meiosis I . Loss-of-function of the ClREC8 leads to watermelon seedless. Disruption of REC8 causes the expression levels of mitosis-related genes and meiosis-related genes decreased through affecting the process of Meiosis I .